Management of the Al-Qur'an Recitation Tahsin Program to Improve the Quality of Students' Al-Qur'an Reading in Tahfidz's House for the Recitation of the Universe - Yunika Safitri (Al-Ulum: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine the planning, implementation and evaluation carried out at the Tahfidz Semesta Koran House. This study uses the type of research field research using a qualitative approach, data collection from this study was obtained by observation and interviews. The findings of this study are: First, the planning is carried out starting from carrying out work meetings / deliberation, activities for accepting new students, determining classes and teachers; Second, the implementation of the tahsin recitation of the Qur'an program which has several stages in its implementation, such as preliminary activities, core activities and closing activities. The method in learning tahsin is using the talaqqi method; Third, the implementation of tahsin itself has two learning evaluations, an evaluation of each ongoing learning and a monthly evaluation.